Study guides

☆☆

Q: Solve 6n + 10 < 4n + 16?

Write your answer...

Submit

Related questions

Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.

6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n

-6n-2n 16 can be solved mathematically getting n = - 2.

The LCM of 4n and 6n is 12n.

The net force is the difference between the 10N falling object and the 4N of air resistance So you solve 10N-4N is 6N

I need to solve this problem using the multiplication principle. -5/6n=-10 solution: -5/6n=-10 (- gets canceled) 5/6n=10 ½=6n N=1/6*2 N=1/12

Is this page of questions from school pupils asking us to do their homework? They are all suspiciously similar in type - only the values differ. However, it's: 6n - 2n = 16 4n = 16 (by completing the subtraction since they are multiples of n) n = 16/4 (change sides, change sign) n = 4. (do the division)

The most force you get is 6+4=10 Newtons.

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

The factors are 2n(4n + 3).

Here is one way. Start with: 4n - 7 = 5 - 2n add 2n to both sides to give: 6n - 7 = 5 add 7 to both sides to give: 6n = 12 divide both sides by 6 to give: n = 2

It can be simplified to: 4m-2n

If you mean: 4n = 1-23-2n then 6n = -22 and so n = 11/3

First we must collect and simplify 'like terms' 2n-6n-36. 2n-6n = -4n Therefore, -4n-36 Take out the greatest common factor. -4 (n+9) Ans = -4 (n+9)

6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3

It is: 4n-13

20n2+6n-2 (4n + 2)(5n -1) This problem can be solved by FOILing. First, multiply the first terms to get 20n2 Next, multiply the outside terms to get -4n. Multiplication of the inside terms results in 10n. Combining -4n and 10n (they are like terms) is 6n. Then, multiply the last terms, to get -2. Combining these answers into one equation gives the answer of 20n2+6n-2.

-2m^4n(8m^3 - 6n^7 - 9)

If: -6n-2n = 16 Then: n = -2

6n+10

It is: -6n+22

2n+4n-12 = 06n-12+12 = 126n = 121/6(6n = 12)n = 2

5n+6n-2n can be solved by combining like terms. Combine 5n and 6n and -2n to get 9n.

6n/10=3 6n=30 n=5

If you mean: -6n-2n = 16 then -8n = 16 and the solution to the equation is n = -2